Studying the effect of temperature and resistances of series (Rs) and parallel (Rsh) on the performance of the solar cell (FTO/Zn2SnO4/CdS:O/CdTe/Cu2Te) using the SCAPS-1D program - Awadh Al-Luhaiby; raad rasool (College of Education for Pure Sciences, 2022)
For the purpose of knowing the effect of temperature, series resistance and parallel resistance on the performance of the solar cell(FTO/ Zn2SnO4/ CdS:O/ CdTe/ Cu2Te)، Using the simulation program SCAPS-1D, the study was carried out in three stages.The first stage of this study is to study the effect of temperature on the parameters of the solar cell،It was found that the efficiency h decreases with increasing temperature. The second stage is to study the effect of series resistance (Rs) as an external factor and it was found that increasing the series resistance reduces the performance of the solar cell The third stage of the study is to study the effect of parallel resistance (Rsh) as an external factor as well on the performance of the solar cell. It was also found that increasing the parallelism resistance improves the performance of the solar cell and increases the output parameters. All phases of the study were installed by installing the default lighting spectrum on the global scale Am1.5, the temperature is 300K, the frequency is 1MHz, and the voltage is 0V. Also, the series resistance (Rs) and the parallel resistance (Rsh) were not activated in the first stage of the research, considering that the cell is an ideal cell.